Vacuolar H(+)-translocating pyrophosphatase is induced by anoxia or chilling in seedlings of rice. - Carystinos, G D (1995)
The present study was undertaken to determine whether vacuolar H(+)-pyrophosphatase (V-PPase) might replace vacuolar H(+)-ATPase under energy stress due to anoxia or chilling in anoxia-tolerant species such as rice (Oryza sativa L.) and corn (Zea mays L.). The relative transcript level of V-PPase in rice seedlings, like that of alcohol dehydrogenase 1, increased greatly under anoxia and declined again when the seedlings were returned to air. However, the distribution of transcripts in root, shoot, and seed differed somewhat from that of alcohol dehydrogenase 1. Immunoreactive V-PPase protein and V-PPase enzyme specific activity in a tonoplast fraction from rice seedlings increased progressively with time of anoxia or chilling at 10 degrees C, showing a 75-fold increase after 6 d of anoxia, compared with a 2-fold increase of vacuolar H(+)-ATPase activity. When the seedlings were returned to air, the specific activity returned to its initial level within 2 d. After 6 d of chilling at 10 degrees C, V-PPase specific activity reached a level 20-fold of that at 25 degrees C. In microsomes of corn roots, V-PPase specific activity did not respond to anoxia but was constitutively high. It is proposed that V-PPase can be an important element in the survival strategies of plants under hypoxic or chilling stress.